What Does the Evidence Tell Us about ‘Thinking and Working Politically’ in Development Assistance? - and Dasandi, Niheer; Laws, Ed; Marquette, Heather; Robinson, Mark (Politics and Governance, 2019)
Abstract: This paper critically reviews evidence on ‘thinking and working politically’ in development. Scholars and practitioners have increasingly recognised that development is fundamentally political, and efforts are underway to develop more politically informed ways of thinking and working. The literature does not yet constitute a strong evidence base to link these efforts to more effective aid programming: much evidence is anecdotal, does not meet high standards of robustness, is not comparative, and draws on self-selected successes reported by programme insiders. We discuss factors commonly considered to explain the success of politically informed programmes in areas where conventional programming approaches fall short. We consider evidence in three areas—political context, sector and organization—and provide guidance on where to focus next. Finally, we outline ways of testing the core assumptions of the ‘thinking and working politically’ agenda more thoroughly, to provide a clearer sense of the contribution it can make to aid effectiveness.